IGF-1R/epithelial-to-mesenchymal transition (EMT) crosstalk suppresses the erlotinib-sensitizing effect of EGFR exon 19 deletion mutations - Vazquez-Martin, Alejandro (Nature Publishing Group, 2013)
Using non-small cell lung carcinoma (NSCLC) cells harboring the erlotinib-sensitizing Epidermal Growth Factor Receptor (EGFR) exon 19 mutation delE746-A750, we developed erlotinib-refractory derivatives in which hyperactive Insulin-like Growth Factor-1 Receptor (IGF-1R) signaling associated with enrichment in epithelial-to-mesenchymal transition (EMT)-related morphological and transcriptional features. We then explored whether an IGF-1R/EMT crosstalk was sufficient to promote erlotinib refractoriness in the absence of second-site EGFR mutations, MET and AXL hyperactivation. Transforming Growth Factor-beta1 (TGFβ1)-induced mesenchymal trans-differentiation was sufficient to impede erlotinib functioning in the presence of drug-sensitive delE746-A750 EGFR mutation. Pharmacological blockade of IGF-1R fully prevented the TGFβ1's ability to activate an EMT protein signature [E-cadherin low/vimentin high]. The sole presence of erlotinib was capable of rapidly activate an IGF-1R-dependent, vimentin-enriched mesenchymal-like phenotype in delE746-A750-mutated epithelial cells. Even if transient, NSCLC cells' intrinsic plasticity to undergo crosstalk between IGF-1R and EMT signaling pathways can sufficiently eliminate the erlotinib-sensitizing effect of highly prevalent EGFR mutations and suggests the urgent need for dual IGF-1R/EMT-targeting strategies to circumvent erlotinib resistance.